Comparison of the clinicopathological features of flat and polypoid colorectal adenomas that are smaller than or equal to five millimeters - ÇELİKEL, ÇİĞDEM (AVES, 2014)
Background/Aims: Colorectal flat adenomas (FAs) may represent a different histogenesis, since their malignant potential is thought to be higher than polypoid adenomas of the same size. In this study, we classified FAs of <= 5 mm into three subgroups-superficially elevated adenomas (SEAs), completely flat adenomas (CFAs), and depressed adenomas (DAs)-based on their low microscopic shapes and compared their clinicopathological features with polypoid tubular adenomas (pTAs) with the same size. Materials and Methods: One hundred one pTAs and 46 FAs with tubular morphology with the same size (<= 5 mm) were studied. Results: The percentages of high-grade dysplasia in FAs and pTAs were 19.56% and 12.87%, respectively. The percentages of the high-grade dysplasia were 28.57%, 13.63%, and 20.00% in the DA, SEA, and CFA subgroups, respectively. FAs had a significantly higher number of normal epithelium at the basal crypts of the lesion than the pTAs (p=0.001). The presence of pericryptal mesenchymal cells was higher in pTAs than the FAs (78.21% vs 10.86%) (p<0.001). Conclusion: Flat adenoma represents a distinct type of colorectal adenoma with special histopathological properties-existence of a normal epithelium at the basal crypts, lack of pericryptal mesenchymal cells, and a high percentage of high-grade dysplasia-especially when it has a depressed shape at low magnification.
Keywords: Flat colorectal adenoma; non-polypoid colorectal neoplasia; colorectal carcinogenesis; colorectal adenoma; colorectal adenomatous polyp; LARGE-BOWEL; COLON; NEOPLASIA; LESIONS; TUMORS; CARCINOMAS; CELLS; CRYPT; TOP